Recent Trends In The Analysis Of Organophosphate Posing (Journal of Pharmaceutical Negative Results, 2023)
Organophosphates (OPs) are a class of chemical compounds that have been widely used in agriculture and industry as pesticides, herbicides, and fungicides. These compounds are known to be toxic to humans and animals, and exposure to high levels of OPs can cause a range of health problems, including neurological damage and cancer. As a result, there has been a growing interest in the analysis of OPs in food, water, and air.Recent trends in the analysis of OPs have focused on developing new and more sensitive analytical methods that can detect low levels of these compounds in complex matrices. One of the most widely used methods for the analysis of OPs is gas chromatography-mass spectrometry (GC-MS). This technique has been used to detect and quantify a wide range of OPs in various matrices, including food, water, and air.Another trend in the analysis of OPs is the use of advanced analytical techniques, such as liquid chromatography-mass spectrometry (LC-MS) and inductively coupled plasma-mass spectrometry (ICP-MS). These techniques offer higher sensitivity and specificity than traditional methods and are able to detect even trace levels of OPs in complex matrices.In recent years, there has also been an increase in the use of sample preparation techniques, such as solid-phase extraction (SPE) and solid-phase microextraction (SPME), to isolate and concentrate OPs from complex matrices. These techniques help to improve the sensitivity and specificity of the analysis and are often used in conjunction with GC-MS, LC-MS, or ICP-MS.Overall, the recent trends in the analysis of OPs have been focused on developing new and more sensitive analytical methods that can detect low levels of these compounds in complex matrices. These methods are playing a crucial role in monitoring and controlling the exposure of humans and animals to OPs and in protecting public health. In India, organophosphates (OPs) have been widely used in agriculture as pesticides and herbicides. The use of these compounds has led to concerns about the potential health effects of exposure, particularly in rural areas where agriculture is a major source of income.